Analisis Literasi , Komunikasi Dan Penalaran Matematika Terhadap Hasil Belajar Siswa Selama Pembelajaran E-Learning Pada Materi Matriks Kelas XI SMA di Sumatera Utara - Riko Kurniawan; Lulu Brygita Silalahi; Cici Limbong; Hardi Tambunan (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to analyze literacy, communication and mathematical reasoning on student learning outcomes during E-Learning learning on Matrix material for Class XI SMA in North Sumatra. This research method uses quantitative and qualitative approaches. The results showed that the sig value for the influence of literacy on learning outcomes was 0.26 > 0.001 and the t value was -2.252 < 0.26, which means that there was no influence of literacy on learning outcomes, then the sig value for the effect of communication on learning outcomes was 0.055 > 0.001 and the t-count value is 1.940> 0.055, which means that there is an effect of communication on learning outcomes. Furthermore, the sig value for the effect of student reasoning on learning outcomes is <0.001 and the t-count value is 7.867> 0.001, which means that there is an effect of reasoning on learning outcomes. In conclusion, there is no influence of literacy on learning outcomes, and there is an effect of communication and mathematical reasoning on learning outcomes during e-learning learning on matrix material in class XI high school students in North Sumatra. Keywords: E-Learning, Literacy Skills, Communication, Reasoning